Prevention of suicides associated with global warming: perspectives from early career psychiatrists - Shoib, Sheikh; Hussaini, Syed Sameer; Armiya’u, Aishatu Yusha’u; Saeed, Fahimeh; Őri, Dorottya; Roza, Thiago Henrique; Gürcan, Ahmet; Agrawal, Aditi; Solerdelcoll, Mireia; Lucero-Prisno III, Don Eliseo; Nahidi, Mahsa; Swed, Sarya; et al. (Frontiers in Psychiatry, 2023)
Climate change poses significant challenges to global mental health, with potential consequences including increased rates of suicide and mental health disorders. Early Career Psychiatrists (ECPs) play a crucial role in addressing these challenges. The Climate Psychiatry Alliance, a group of psychiatrists dedicated to improving mental health amidst climate change, recognizes the importance of cultivating climate-aware ECPs. Training ECPs to become confident climate-aware clinicians enables them to effectively treat patients experiencing anxiety, depression, and PTSD in the context of climate-related distress. Together with other mental health professionals, ECPs can contribute to efforts by implementing strategies for monitoring and treating mental health problems arising from climate events. Additionally, they can raise awareness about the psychological consequences and risks of suicide associated with climate change. Collaboration among ECPs from various regions is essential in developing community-based approaches and reducing vulnerabilities. ECPs must prioritize supporting vulnerable populations by advocating for increased funding for mental health support and research in affected areas. Long-term solutions to address the mental health impacts of climate change and global warming should be pursued to mitigate future suicidality. Integrating climate considerations into local mental health programs and expanding psychological support services is crucial. By promoting emotional resilience and self-awareness, ECPs can contribute to building a more climate-resilient and mentally healthy society.